2012
DOI: 10.1177/1087054712453168
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficits in Children With Combined Autism and ADHD

Abstract: The findings underscore the importance of including measures of attention and intellectual function when assessing children with the combination of ASD and ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 62 publications
4
31
2
Order By: Relevance
“…However, most prior studies have had modest sample sizes, lacked consideration of a range of potentially confounding factors, and have focused on children of school-age or older (Ehlers et al 1997; Geurts et al 2004; Corbett and Constantine 2006; Lundervold et al 2012; Jang et al 2013; Rao and Landa 2014). The few studies focusing on young children have been based on clinically-ascertained samples (Visser et al 2016), which likely have limited generalizability given noted skewed severity distributions in such samples (Rao and Landa 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, most prior studies have had modest sample sizes, lacked consideration of a range of potentially confounding factors, and have focused on children of school-age or older (Ehlers et al 1997; Geurts et al 2004; Corbett and Constantine 2006; Lundervold et al 2012; Jang et al 2013; Rao and Landa 2014). The few studies focusing on young children have been based on clinically-ascertained samples (Visser et al 2016), which likely have limited generalizability given noted skewed severity distributions in such samples (Rao and Landa 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The ASD group with ADHD was found to have more problems in inhibitory performance but not in the working memory task compared to the ASD group without ADHD symptoms [18] . The combination of ASD and ADHD has also been associated with poorer attention than ASD alone [19] . Thus, ADHD symptoms have been suggested to have an additive effect on EF.…”
Section: Introductionmentioning
confidence: 99%
“…Results suggested that children with ASD+ADHD had an "additive" profile rather having a qualitatively distinct distinctive pattern of deficits. Similarly, Lundervold et al (2016) found that the ASD+ADHD group had a higher variability. Adamo et al (2014) assessed the influence of comorbidity on response time intra-subject variability (RT-ISV), in children with ASD, ASD+ADHD, ADHD and TD using a sustained attention task.…”
Section: Attentionmentioning
confidence: 84%
“…Moreover, examining different attentional constructs, children with ASD+ADHD differed from TD children especially on sustained attention and alertness (Adamo et al, 2014;Andersen et al, 2013;Sinzig et al, 2008a;Lundervold et al, 2016;Tye et al, 2014). Some studies evidence that the comorbid group is the group with the most pronounced brain function abnormalities (Chantiluke et al, 2014) and more impaired on daily-life executive functioning (Dajani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation